PEMBELAJARAN MATEMATIKA BERBASIS INQUIRY PADA SISWA SMP NEGERI 3 PAGARALAM - Ria Erviana; Novi Susanti (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to determine student learning outcomes after applying inquiry-based learning on the subject of surface area and volume of cubes and blocks. The method used is a quasi-experimental method in the one-shot case study category. Data collection techniques using tests / essay questions. Then the data were analyzed descriptively. After the research was conducted, the student learning outcomes at the first meeting were with an average of 82.3, and at the second meeting had an average value of 84.5, and data analysts on the final test had a class average of 86.5 who entered in very good category. So, from the results of the study it can be concluded that inquiry-based learning has a positive influence on learning in the classroom, because it can improve student learning outcomes and make students more active in learning.